A primer on governance and performance in small and medium-sized enterprises - Enrique Yacuzzi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
This paper is a primer on corporate performance, corporate governance, and their interrelationships and measurement systems, with particular focus on Small and Medium- Sized Enterprises (SMEs). This is the first report of a larger on going research project. In the domain of performance measurement the paper describes the trend from financial to non-financial measures, as well as a taxonomy of measures and the impact of the TQM movement on measurement practices. In the domain of governance, governance as a general concept is presented, followed by the more specific concept of corporate governance. Four theories of corporate governance are explained, along with literature findings on the relationship between corporate governance and corporate performance, with reference to both works on large firms and works on SMEs.
Keywords: G30; G34; L25; M11; 330; corporate governance; corporate performance; measurement; small and medium-sized enterprises (SMEs); KMU; Corporate Governance; Unternehmenserfolg